Surgical treatment of peri-prosthetic femur fractures with dedicated NCB plates: our experience - Molinari, Giam Paolo; Giaffreda, Graziella; Clementi, Daniele; Cabbanè, Giuseppe; Galmarini, Valter; Capelli, Roberto Maria (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: The incidence of periprostethic femur fractures has increased over the last years; the treatment includes an open reduction and internal fixation or revision implant. The treatment of these fractures can be complex, expensive and associated with risks of systemic and local complications. Methods: We evaluated clinical and radiological results in patients treated in our department for periprosthetic femoral fractures from 2011 to 2017. We included 52 cases of periprosthetic fractures regardless of their classification with a mean follow-up of 2 years. The analisys of the result was performed using Harris Hip Score and searching for radiographic signs of loosening, infections or mechanical failure of the implants. Results: There was no evidence of septic complications or mechanical failure in cases treated. The average HHS was equal to 92 points with a certificate pain relief and a sufficient independence in daily living activities. Conclusions: The treatment of periprosthetic fractures is complex: it depends on type of fracture, on stability of the stem and on the bone quality. A right classification of the fractures, a good experience of the surgeon in prosthetic and trauma surgery is the basis for the best treatment.